Foucault and «power in its cynical state»: from naked governmentality to risible monarchy - Freitas, Juan Horacio de (Pensamiento. Revista de Investigación e Información Filosófica, 2025)
This paper departs from a basic premise: the analysis that Foucault devotes exclusively to Cynicism in the last of his courses at the Collège de France is preceded by his concern over the phenomenon of cynical power, which has appeared repeatedly, although scattered, throughout the Foucauldian repertoire since the early seventies. We will attempt at demostrating that this precedent is not casual, so we will examine the link between the way in which such particular power is depicted and the studies that Foucault undertakes on Cynicism in his last years of intellectual production. This examination will allow us to carry on with the project inaugurated by Foucault of developing a history of Cynicism understood as a historical category associated with the «scandal of truth».